Identification and Characterization of Methyl Isoeugenol Compound from the Golden Yellow Hued Muga Silk Fiber of India. Issue 8 (3rd August 2021) - Choudhury, Manasee; Ramakrishnan, Elancheran; Devi, Dipali
ABSTRACT: Organic extraction of pigmentation constituents of the cocoons of Antheraea assamensis (muga) was investigated in this study. Chemical extraction of muga cocoon fibers and their host plant som ( Machilus bombycina ) leaves were carried out using two benign solvents: hexane and ethyl acetate. Thin-layer chromatography (TLC) revealed the presence of methyl isoeugenol and isoeugenyl acetate from extracts of cocoon fiber and som leaves, respectively. The compounds were further confirmed by gas chromatography-mass spectroscopy (GC-MS) and nuclear magnetic resonance (NMR) analysis. Methyl isoeugenol is a yellow colored compound, which resembles the color of the muga fiber and may be responsible for coloration of the same. It is anticipated that isoeugenyl acetate (also known as isoeugenol acetate), a phenylpropanoid compound present in the host plant might be converted to methyl isoeugenol during the course of metabolism in the silkworm larva, which in turn may be responsible for production of golden yellow colored silk fiber for building the cocoons. The present investigation might help to utilize methyl isoeugenol as a potential dyeing material for other fabrics in the industry thus providing a new dimension into the textile field.